2018
DOI: 10.5861/ijrsp.2018.3019
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and other factors behind examination performance of college students

Abstract: Studies on happiness had flourished around the world. Different impacts of happiness in different aspects of life had been well documented. In the Philippines however, the study of happiness remained scarce especially in academic setting. In addition, most previous studies focused mainly on GPA as a measure of academic performance. Because happiness is vulnerable to life experiences (Veenhoven, 1997), linking happiness with GPA may not yield a comprehensive and more meaningful result. To fill this gap in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Different studies that were conducted in various countries including Pakistan, Iran, support our study finding that happiness and academic performance have strong and positive association and agree with our study finding that increase in happiness leads to better academic performance among students [8], [9]. While a study that conducted in Philippines reported conflicting finding, that happiness has no impact on academic performance of students [3]. In the presence of findings in literature regarding the association of happiness and academic performance, that agrees with our study results, we support the idea that by increasing happiness we may be able to bring enhancement in the academic performance of students.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Different studies that were conducted in various countries including Pakistan, Iran, support our study finding that happiness and academic performance have strong and positive association and agree with our study finding that increase in happiness leads to better academic performance among students [8], [9]. While a study that conducted in Philippines reported conflicting finding, that happiness has no impact on academic performance of students [3]. In the presence of findings in literature regarding the association of happiness and academic performance, that agrees with our study results, we support the idea that by increasing happiness we may be able to bring enhancement in the academic performance of students.…”
Section: Discussionsupporting
confidence: 90%
“…In either way, it has direct influential effects on everyday life situations [7]. As mentioned above that happiness is considered as either a state of positive emotions or state of satisfaction, this may be the reason that happier people are better able to confront various life situations as compared to unhappy ones and subsequently give better performance in daily life activities [3], [4]. Academic performance depicts intellectual growth and development of a student, bringing to light the ambition of entire educational structure [8].…”
mentioning
confidence: 99%
“…The finding further suggests that low and high academic outcome does not imply considerable variability in students' happiness. The previous investigation (Lumontod, 2018) found the same result. The latter study suggests that happiness was not associated with students' examination performance.…”
Section: Happiness and Academic Performancesupporting
confidence: 79%
“…In some studies, happiness was inconsistently related to students' academic performance (Bücker et al, 2018). The previous study also found similar results suggesting that happiness did not predict college students' examination performance (Lumontod, 2018). The inconsistency of the findings may suggest two things.…”
Section: Happiness and Academic Performancementioning
confidence: 91%
“…Human behavior and productivity are influenced by happiness. Therefore, later research has investigated the predictive ability of happiness on multiple dimensions of human activity, including academic performance (Lumontod, 2018). Students in Latin America have a decline in academic performance largely due to the obligation to help their parents earn a living.…”
mentioning
confidence: 99%